Ground heating and methane oxidation processes at shallow depth in Terre Calde di Medolla (Italy): Observations and conceptual model. Issue 5 (19th May 2015) - Capaccioni, Bruno; Tassi, Franco; Cremonini, Stefano; Sciarra, Alessandra; Vaselli, Orlando
Abstract The toponym "Terre Calde di Medolla" (literally, "Warm Earths of Medolla") refers to a farming area, located near the town of Modena (Emilia‐Romagna region, northern Italy), which has always been known by the local population for the relatively high temperatures of the soil. This phenomenon is particularly evident in wintertime when the snow cover over this area rapidly melts. A detailed investigation, carried out after the devastating 2012 Emilia earthquake that affected this area, showed soil temperatures up to 44°C, i.e., 20–25°C above the local background value, together with diffuse soil fluxes of CH4 (0–2432 g × m−2 × d−1) and minor, though significant, CO2 (0–1184 g × m−2 × d−1), especially from subcircular (a few meters in diameter) zones. Ground heating and gas seepage appear spatially correlated, thus suggesting a close relationship between the two phenomena. The anomalous high ground temperature is not associated with an anomalous geothermal gradient or with the uprising of deep‐seated hot fluids. According to the lateral and vertical distributions of the temperatures as well as the chemical and isotopic compositions of the soil gases, the most reliable explanation is the exothermic oxidation of diffusely uprising biogenic methane at very shallow levels (<1 m). Such a process occurs in the presence of free oxygen and methanotrophic bacteria and can then explain (i) the observed ground heating up, (ii) the diffuse emission from the soil of CO2 characterized by an extremely negative isotopic (13C/12C) signature, and (iii) the lack of diffuse and low CH4 fluxes. According to these hypotheses, the heating phenomena affecting the shallow groundwater and the ground surface, as described by several witnesses in the area of the May–June 2012 Emilia earthquake, could be related to either a coseismic or postseismic onset of new areas affected by CH4 seepage or an increase in preexisting CH4 fluxes.